1994
DOI: 10.1113/jphysiol.1994.sp020300
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intracellular anions on ATP‐dependent potassium channels of rat skeletal muscle.

Abstract: 1. We have used excised inside-out patches to study the effects of anions bathing the cytoplasmic surface of the membrane on ATP-dependent K+ channels of rat flexor digitorum brevis muscle. Channels were closed by ATP applied to the cytoplasmic face of the patch with a concentration for half-closure (K1) of 14 ,UM, were highly selective for K+ and had unitary conductances of 62 pS in symmetrical 155 mm K+ and 27 pS in 5 mM[K+]o.2. In 139 mm Cl-internal solution channel activity declined rapidly after excision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(25 citation statements)
references
References 61 publications
3
22
0
Order By: Relevance
“…These results suggest that although phosphorylation may be a part of the regulatory process, additional key elements are involved. In rat skeletal muscle cells, KATP was found to be activated by high concentrations (Ͼ50 mM) of gluconate, with the effect proportional to the length of the carbon chain (13). This finding suggested to us the hypothesis that native anionic FIG.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…These results suggest that although phosphorylation may be a part of the regulatory process, additional key elements are involved. In rat skeletal muscle cells, KATP was found to be activated by high concentrations (Ͼ50 mM) of gluconate, with the effect proportional to the length of the carbon chain (13). This finding suggested to us the hypothesis that native anionic FIG.…”
Section: Discussionmentioning
confidence: 77%
“…Mg 2ϩ was found to be necessary for ATP activation of KATP; therefore, many researchers speculated that phosphorylation/dephosphorylation was the key to maintenance of KATP channel activity (16). Mg-ATP, however, was often ineffective in activating KATP in rat skeletal muscles (13). In addition, intensive searches for protein kinases and the protein phosphorylation targets have not been successful (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We think this unlikely for several reasons. In the first place, the structurally related compound, dequalinium, has previously been shown not to block voltage-gated Ca2" channels in sympathetic neurones at concentrations up to 10 gM (Dunn, 1994 (Habermann & Fischer, 1979;Hugues et al, 1982;Habermann, 1984) and more recent work has shown that intracellular anions also affect the activity of a number of K+ channels, as well as their sensitivity to blocking agents (Zhang et al, 1994;Heath & Terrar, 1994;McKillen et al, 1994 (Wadsworth et al, 1994). This evidence is clearly consistent with the existence of SKCa channel subtypes.…”
Section: Effect Of Ucl 1530 On Guinea-pig Sympathetic Neuronesmentioning
confidence: 99%